Волонтерський рух і його роль у сучасній Україні - Філатова, А. С. (ХНУРЕ, 2022)
The subject of the article is the study of the volunteer movement and its role in Ukraine in such a difficult period. It also describes how volunteer organizations work. What are the most popular types of volunteering today. Volunteering in Ukraine and abroad.